2016
DOI: 10.1016/j.athoracsur.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of Failed Pulmonary Autografts Compared With Normal Pulmonary Roots

Abstract: Failed pulmonary autografts retained nonlinear response to mechanical loading typical of healthy human arterial tissue. Remodeling increased wall thickness but decreased wall stiffness in failed autografts. Increased compliance may explain progressive autograft root dilatation in autograft failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 29 publications
4
36
0
Order By: Relevance
“…Availability of explanted pulmonary autograft specimens offered a unique opportunity to study the biomechanical consequences of remodeling after the Ross operation. In a previous study, altered biomechanical characteristics were shown in explanted autografts compared with native pulmonary roots at pulmonary pressures [12]. In this study, we have demonstrated that autograft roots, explanted after progressive dilatation, did not remodel to represent native aortic roots biomechanically at systemic pressures in this patient population.…”
Section: Commentsupporting
confidence: 48%
See 1 more Smart Citation
“…Availability of explanted pulmonary autograft specimens offered a unique opportunity to study the biomechanical consequences of remodeling after the Ross operation. In a previous study, altered biomechanical characteristics were shown in explanted autografts compared with native pulmonary roots at pulmonary pressures [12]. In this study, we have demonstrated that autograft roots, explanted after progressive dilatation, did not remodel to represent native aortic roots biomechanically at systemic pressures in this patient population.…”
Section: Commentsupporting
confidence: 48%
“…Understanding the biomechanics of vascular remodeling in explanted autografts is important for designing strategies to prevent dilatation. We previously demonstrated that vascular remodeling in explanted autografts resulted in increased compliance compared to native pulmonary roots at pulmonary pressures [12]. We hypothesized that pulmonary autografts explanted after progressive dilatation were also more compliant than native aortic roots at systemic pressures.…”
mentioning
confidence: 98%
“…Our results show that a valveless pulmonary autograft placed in aortic position will remodel such that its macroscopic behavior leans more towards aorta-like behavior, as measured through planar biaxial tensile tests. In contrast, when studying excessively dilated pulmonary autografts in ten patients, Mookhoek et al [11,12] observed a decreased stiffness compared to both the native aorta and pulmonary artery, suggesting a failure of the tissue to remodel. Developing a mathematical model about this phenomenon may help to understand neoaortic valve failures, assuming that pulmonary (neoaortic) root dilatation is a major determinant of neoaortic valve regurgitation.…”
Section: Introductionmentioning
confidence: 93%
“…The study of Mookhoek et al (50) adds a piece in the puzzle of the mechanical phenomena related to the dilatation of pulmonary autograft under systemic conditions. The authors focused their attention on the idea that failed pulmonary autografts retained nonlinear response to mechanical loading typical of healthy human arterial tissue, as nonlinear stress-strain response was present in both failed autografts and normal pulmonary roots.…”
Section: Biomechanical and Biological Insights Of The Pulmonary Failurementioning
confidence: 99%
“…The authors applied the mathematical-physical model in which the explanted autograft and pulmonary roots were assumed incompressible and nonlinear hyper-elastic materials (50). They found that non-linear stress-strain response was present in both failed and normal pulmonary roots, but remodeling increased wall thickness and decreased stiffness in the failed specimens after Ross operation.…”
mentioning
confidence: 99%